Improving Mathematics Learning Outcomes Using Pipette Media in Students at SDN 17 Kuala Mandor B - Suharno Suharno (Universitas Tanjungpura, 2020)
This research was a classroom action research conducted in three cycles, each cycle consisting of planning, action, observation, and reflection. The aspects observed in each cycle were the activities of students and teachers, as well as the learning process of the subject matter in fractions using a simple medium named Pipette. The subjects were 15 students. The results of the study of students' abilities in the chapter of fractions, each cycle has increased. Cycle I, the average score of students was 51.93 with a percentage of completeness 13.33%. Students who reached KKM were 2 students. Based on the result of cycle I and cycle II, the average score of 85 students with a percentage of completeness 86.67%. Students who reached KKM were 13 students. From the two cycles applied, there was an increase in the ability of students in the subject matter of fraction addition. Based on the indicators of success in the second cycle, that the applied papita media can improve the ability of students in the chapter of fraction addition in V grade students of SDN 17 Kuala Mandor B, Kubu Raya Regency.